2012
DOI: 10.1016/j.mrgentox.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The use of next generation sequencing technology to study the effect of radiation therapy on mitochondrial DNA mutation

Abstract: The human mitochondrial genome has an exclusively maternal mode of inheritance. Mitochondrial DNA (mtDNA) is particularly vulnerable to environmental insults due in part to an underdeveloped DNA repair system, limited to base excision and homologous recombination repair. Radiation exposure to the ovaries may cause mtDNA mutations in oocytes, which may in turn be transmitted to offspring. We hypothesized that the children of female cancer survivors who received radiation therapy may have an increased rate of mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 37 publications
(51 reference statements)
2
39
0
Order By: Relevance
“…36 In addition to forensic applications, heteroplasmic mtDNA variants have been considered useful genetic markers for genetic disease diagnosis, cancer prognosis, and other research studies. 17,18,37,38 Knowing the limitation of the MPS technologies and the interference of NUMTs and SNPs, evaluation and interpretation of mtDNA sequence results should be carried out with caution. When paraffin-fixed tumor tissues are used and target enrichment is limited to the use of multiple pairs of primers for PCR enrichment, 18 interference of NUMTs and SNPs is significant, and cautious interpretation of results derived from these approaches is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…36 In addition to forensic applications, heteroplasmic mtDNA variants have been considered useful genetic markers for genetic disease diagnosis, cancer prognosis, and other research studies. 17,18,37,38 Knowing the limitation of the MPS technologies and the interference of NUMTs and SNPs, evaluation and interpretation of mtDNA sequence results should be carried out with caution. When paraffin-fixed tumor tissues are used and target enrichment is limited to the use of multiple pairs of primers for PCR enrichment, 18 interference of NUMTs and SNPs is significant, and cautious interpretation of results derived from these approaches is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a decrease in mtDNA content has been reported as a result of radiotherapy in cancer patients [191]. However, another study found no evidence that radiotherapy for pediatric cancer, which resulted in scatter radiation to the ovaries, is associated with the mitochondrial genome mutation frequency in female cancer survivors and their children [192]. In conclusion, mtDNA mutations (induced by radiotherapy or germline) can also affect the response and therefore the outcome of radiotherapy although the precise role and mechanisms are not yet fully understood.…”
Section: Radiation Therapymentioning
confidence: 99%
“…In recent years, high-throughput sequencing technologies have matured in step with reduced costs. The high-coverage generated by the new high-throughput sequencing methods provides a powerful tool for the study of mtDNA heteroplasmy (Guo et al, 2012a; Tang and Huang, 2010). …”
Section: Introductionmentioning
confidence: 99%